Antara Regulasi dan Realita: Problematika Penerapan TKDN dalam Pengadaan Konstruksi Pemerintah di Indonesia - Fallach, Teuku Zikril; Khairani, Khairani; Syofiarti, Syofiarti (Nagari Law Review; Vol 9 No 1 (2025): Nagari Law Review, 2025)
The Domestic Component Level (TKDN) policy aims to strengthen Indonesia's domestic industries through government procurement. However, implementation in public construction projects often fails to meet expectations. This study evaluates TKDN compliance, identifies causes of non-compliance, and assesses administrative enforcement effectiveness using a juridical-empirical approach on five strategic infrastructure projects under Balai Jasa Konstruksi Wilayah I (BJKW I) Banda Aceh. Findings reveal significant implementation gaps: two of five projects failed to meet TKDN thresholds per Minister Decree No. 602/KPTS/M/2023, including one with zero percent realization, yet no sanctions were imposed. Four systemic factors cause non-compliance: low technical literacy among contractors, inadequate documentation infrastructure, weak supervision by project owners, and absent enforcement mechanisms. The study identifies an "enforcement deficit" where legal norms lose regulatory power due to inconsistent application. This creates unfair competition where compliant contractors gain no advantage while violators face no consequences. Research confirms Van Meter and Van Horn's implementation theory, showing policy success requires implementer capacity, inter-organizational communication, and enforcement consistency. The study recommends five strategic measures: integrated real-time verification systems, comprehensive capacity building, cross-agency coordination units, automatic sanctions, and positive incentives for compliance. Transformation from compliance-oriented to performance-oriented implementation is essential for achieving TKDN's industrial strengthening objectives .